Enhancing Early English Vocabulary for 5-6 Year-Olds Through Quizlet Application - Warmansyah, Jhoni; Suzanne, Nina; Hendriani, Suswati; Annisa, Nur; Agusniwati, Fiola (Journal of Islamic Education Students (JIES), 2023)
The Utilization of Digital Applications in Education Facilitates the Teaching and Learning Process. Quizlet, as one such application for language learning, is examined in this research to assess its effectiveness in enhancing Early English vocabulary for 5-6 years old. The research employs a quantitative method through surveys, collecting data via questionnaires based on theoretical frameworks. Results indicate that the use of Quizlet enhances English vocabulary for young children, as evidenced by their recognition of English words. This suggests that Quizlet can aid teachers in introducing English to early learners, providing an alternative method to improve English vocabulary for young children. Future research may explore further developments in the utilization of similar applications.